The journey of intercultural adaptation : experiences and perspectives of international students - Kemppainen, Elise Yoong Tian (2019)
This study explores the experiences and perspectives of postgraduate international students. Its key objective is to understand the lived experience and internal processes involved in adaptive change. It aims to examine different individual stories in order to map out the journey of intercultural adaptation. For the study of personal stories, the narrative approach is adopted. This study uses a data set from a case study on the study experiences of students from international Master’s Degree programmes at Jyväskylä University. Individual stories are collected and narratives co-constructed. The Dialogical Narrative Analysis (DNA) method is used to derive a typology of ideal types. The analysis process delves into the prior expectations, real-life experiences, reflections as well as the variety of emotions expressed. The findings point to a variety of adaptation challenges and psychological adaptive tools and strategies. In particular, experiences of difference and ambivalence were repeatedly described. The typology of seven ideal types derived illustrates The Adaptation Epic as follows: The Journey, Chaos and Order, The Hero, Transcendence, Alchemy, Meditation and Rebirth. To summarise, adaptive change involves a journey between order and chaos, in which the hero explores dichotomies and ambivalence and performs acts of transcendence, alchemy and meditation. The outward journey into the Other is in fact an inward journey into the self, which ultimately culminates in a rebirth. Lastly, this study affirms the potential of the narrative approach for intercultural research.